IMPLEMENTASI SISTEM MONITORING SUHU TUBUH BERBASIS SMARTPHONE MENGGUNAKAN MIKROKONTROLER ARDUINO VIA BLUETOOTH - pratiwi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
As technological developments are more advanced and open with the current globalization as now, it is expected that advanced technology can provide convenience in all areas, such as measurement and temperature monitoring for example. Therefore, it takes a tool that serves to convert the amount of heat into a quantity of electricity that can easily be analyzed amount of temperature sensors. This research begins with the human body temperature that will be detected by arduino microcontroller temperature sensor. The receiver interacts the detection device using the LM35 temperature sensor. The result of the temperature change will be read and processed on the arduino microcontroller.In testing the accuracy of body temperature value, temperature measurement is done by putting the body temperature sensor LM35di body part that is neck, mouth, right armpit, armpit left, chest and back.That The measurement of the temperature sensor that is LM35 compared to the thermometer, is able to work well. The percentage error rate of the temperature sensor is 0%. According to the LM35 sensor testing compared to a thermometer, having a temperature range difference is zero comma, so the results of the measurement are still in tolerance. Keywords: Temperature Sensor, Arduino, Bluetooth